Evaluating Faith and Modernity: Old Testament Theology in the Context of Contemporary Christian Education - Sitorus, Herowati (Journal Evaluation in Education (JEE), 2026)
Purpose of the study: This study explores the evolving role of evaluative processes in Christian education, with a focus on the intersection of Old Testament theology and contemporary theological thought. It seeks to understand how evaluations in theological and Christian education reflect broader shifts in how faith, modernity, and the relevance of Old Testament principles are understood in contemporary contexts. Methodology: Employing a qualitative approach, this research uses a literature review. It examines secondary sources, including Scopus-indexed journals, to trace the development of evaluation within Christian education and Old Testament theology. Primary sources include books analyzing shifts and tensions in theological evaluation, historical contexts, political influences, and the changing positions of Christian congregations. Main Findings: The study reveals that evaluation serves as a tool that significantly influences the trajectory of theological discourse, particularly regarding the Old Testament. It highlights the interconnectedness of theology and various facets of human life, emphasizing the importance of critical evaluation, empathy, and reflection in contemporary theological engagement. Novelty/Originality of this study: This research offers a fresh perspective by examining Old Testament theology as an evaluative space within Christian education and its connection to contemporary theological debates. It distinguishes itself by focusing on the evaluative nature of Old Testament theology, in contrast to previous research that emphasizes historical contexts or the weaknesses of objectivist lenses. It seeks to provide unique insights into the ongoing relevance of Old Testament principles in shaping contemporary theological evaluations and practices within Christian education.